Revealing Layer‐Specific Ultrastructure and Nanomechanics of Fibrillar Collagen in Human Aorta via Atomic Force Microscopy Testing: Implications on Tissue Mechanics at Macroscopic Scale. Issue 5 (10th February 2022) - Asgari, Meisam; Latifi, Neda; Giovanniello, Francesco; Espinosa, Horacio D.; Amabili, Marco
Abstract : Soft biological tissues are natural biomaterials with structures that have evolved to perform physiological functions, for example, conferring elasticity while preserving the mechanical integrity of arteries. Furthermore, the mechanical properties of the tissue extracellular matrix (ECM) significantly affect cell behavior and organ function. ECM mechanical properties are strongly affected by collagen ultrastructure, and perturbations in collagen networks can cause tissue mechanical failure. It is thus crucial to understand the ultrastructural mechanical properties of soft tissues. Herein, the ultrastructural and nanomechanical properties of arterial tissues are reported. Specifically, maps of aorta tissue stiffness in its three constitutive layers, namely tunica intima, media, and adventitia, are reported. Atomic force microscopy (AFM) with large and ultrasharp tips is used to explore tissue stiffness at two scales. Quasistatic tensile tests are further conducted to understand a potential correspondence between small‐scale mechanical properties obtained via AFM indentation and macroscopic behavior of the tissue at low and large strains. Furthermore, gradients in stiffness across the various layers as well as deformation rate effects are investigated. It is envisioned that the established methodology serves as a tool to investigate the effect of ECM remodeling associated with vascular diseases such as aneurysms and arterial stiffening linked to hypertension. Abstract : Ultrastructural and nanomechanical properties of arterial tissues are obtained using atomic force microscopy (AFM). Tensile tests are performed to understand the correspondence between small‐scale tissue properties obtained via AFM and tissue macroscopic behavior. Stiffness gradients across aortic layers and deformation rate effects are also explored to establish a methodology to investigate effects of extracellular matrix remodeling associated with vascular diseases.